Blockchain for Supply Chain Management: To Enhance Transparency, Traceability, and Efficiency - Hamza Asmaeil Almabrok (African Journal of Advanced Pure and Applied Sciences, 2023)
The global landscape of supply chain management is undergoing a transformation driven by the integration of blockchain technology. This research paper delves into the profound impact of blockchain in the realm of supply chain management, with a primary focus on enhancing transparency, traceability, and efficiency across diverse industries. As supply chains become increasingly complex and interconnected, the need for innovative solutions to address challenges such as fraud, counterfeiting, and inefficiency has become paramount. Blockchain, as a decentralized and immutable digital ledger, holds the potential to revolutionize supply chain operations by providing a transparent and tamper-resistant record of transactions and product movements. This paper explores the fundamental principles of blockchain technology and its applicability to supply chains. Real-world case studies and industry examples are examined to illustrate the tangible benefits and outcomes of blockchain integration. However, the adoption of blockchain in supply chain management is not without its challenges. Scalability, interoperability, and regulatory concerns are among the hurdles that must be overcome. In addressing the research question, "How can the integration of blockchain technology into supply chain management enhance transparency, traceability, and efficiency across various industries?", this paper provides a comprehensive analysis of the current landscape and future prospects of blockchain technology in supply chain management. By the conclusion of this research journey, it is evident that blockchain is not merely a technological innovation but a transformative force capable of instilling trust and integrity into the very core of global supply chains.